Bio-stimuli-responsive multi-scale hyaluronic acid nanoparticles for deepened tumor penetration and enhanced therapy. (1st September 2017) - Huo, Mengmeng; Li, Wenyan; Chaudhuri, Arka Sen; Fan, Yuchao; Han, Xiu; Yang, Chen; Wu, Zhenghong; Qi, Xiaole
Highlights: Multi-scale HA nanoparticles encapsulated with PAMAM dendrimers were developed. The fine bio-stimuli-responsive properties of HA/PAMAM nanoparticles was verified. The in vitro tumor spheroids deeply penetration of HA/PAMAM-FITC was confirmed. HA/PAMAM-FITC showed prolonged systematic circulation in mice bearing H22 tumor. HA/PAMAM-MTX demonstrated higher antitumor activity in H22 sarcoma mice. Abstract: In this study, we developed bio-stimuli-responsive multi-scale hyaluronic acid (HA) nanoparticles encapsulated with polyamidoamine (PAMAM) dendrimers as the subunits. These HA/PAMAM nanoparticles of large scale (197.10 ± 3.00 nm) were stable during systematic circulation then enriched at the tumor sites; however, they were prone to be degraded by the high expressed hyaluronidase (HAase) to release inner PAMAM dendrimers and regained a small scale (5.77 ± 0.25 nm) with positive charge. After employing tumor spheroids penetration assay on A549 3D tumor spheroids for 8 h, the fluorescein isothiocyanate (FITC) labeled multi-scale HA/PAMAM-FITC nanoparticles could penetrate deeply into these tumor spheroids with the degradation of HAase. Moreover, small animal imaging technology in male nude mice bearing H22 tumor showed HA/PAMAM-FITC nanoparticles possess higher prolonged systematic circulation compared with both PAMAM-FITC nanoparticles and free FITC. In addition, after intravenous administration in mice bearing H22 tumors, methotrexate (MTX) loaded multi-scale HA/PAMAM-MTX nanoparticles exhibited a 2.68-fold greater antitumor activity.